Bound by love - Rogers, Rosemary (Don Mill, Ont. : HQN, 2009)
Leoida, the illegitimate daughter of the Russian czar, arrives at the estate of Stefan, the Duke of Huntley, with a mission and secrets. She searches for covert documents in Stefan's library and the two become tangled in a web of espionage and deceit.
This edition published by arrangement with Harlequin Books S.A. --T.p. verso.
Keywords: Historical fiction; Love stories